Pembangunan Kesadaran Ketenagakerjaan Melalui Pendidikan Serikat Pekerja di PT. Steel Center Indonesia - Danang Apri Asmoro; Arista Candra Irawati (PSHPM Untag Semarang, 2026)
Employment relations are essentially legal relations that create rights and obligations for both workers and employers. In industrial relations practice, the existence of legal norms and Collective Labor Agreements has not always been followed by an adequate level of worker understanding regarding their substance, function, and consequences. This condition causes workers’ employment awareness to develop suboptimally, even though such awareness is essential for creating orderly, fair, harmonious, and productive industrial relations. At PT. Steel Center Indonesia, this problem is reflected in the fact that some trade union members do not yet fully understand their employment rights and obligations, have not regarded the Collective Labor Agreement as a strategic instrument of protection, and have not shown strong organizational participation in supporting trade union regeneration. Therefore, trade union education becomes an important means of building an understanding of labor law and fostering organizational awareness in the workplace. This paper aims to analyze the role of trade union education in developing workers’ employment awareness at PT. Steel Center Indonesia. The method used is normative juridical with an empirical juridical approach. The results show that trade union education plays a strategic role in improving members’ understanding of rights and obligations in employment relations, strengthening their understanding of the Collective Labor Agreement, and encouraging member participation and organizational regeneration. Thus, trade union education is an important instrument in building employment awareness and needs to be developed systematically to support the creation of healthy and just industrial relations